2017
DOI: 10.1186/s12977-017-0354-5
|View full text |Cite
|
Sign up to set email alerts
|

Highly divergent patterns of genetic diversity and evolution in proviral quasispecies from HIV controllers

Abstract: BackgroundOngoing intra-host HIV-1 evolution has been shown in individuals that naturally suppress the viremia to low levels (HIV controllers) by the analysis of the RNA in plasma compartment. Detection of evolution at the DNA proviral compartment in HIV controllers, however, has been more challenging and the precise correlation between the systemic viral suppression level and rate of reservoir’s reseeding in those individuals is not fully understood. In this sense, we examined the proviral DNA quasispecies by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 53 publications
(65 reference statements)
7
59
0
Order By: Relevance
“…Prediction of coreceptor usage showed that most individuals (17/22; 77%) presented only R5-tropic viruses, while five individuals presented X4/R5X4-tropic viruses. The prevalence of R5-tropic viruses was similar to the 78% prevalence found by de Azevedo et al [ 114 ] in another Brazilian cohort.…”
Section: Discussionsupporting
confidence: 89%
“…Prediction of coreceptor usage showed that most individuals (17/22; 77%) presented only R5-tropic viruses, while five individuals presented X4/R5X4-tropic viruses. The prevalence of R5-tropic viruses was similar to the 78% prevalence found by de Azevedo et al [ 114 ] in another Brazilian cohort.…”
Section: Discussionsupporting
confidence: 89%
“…A higher median of divergence was observed for nef (0.6% per year), suggesting that nef has a greater potential for viral diversity than does gag, in agreement with previous studies showing greater conservation of gag [ 71 , 72 ]. Previous observations from our group of lower quasispecies diversity for the env gene from EC samples in comparison to VCs [ 73 ] and the low, but similar, median values of divergence in gag and nef for viral samples from ECs and VCs in the present study indicate that lower levels of viral replication restrict evolution.…”
Section: Discussionsupporting
confidence: 85%
“…Although most HICs have plasma viral loads below the limit of detection of commercial assays, basal viral replication levels can be detected by ultrasensitive methods [ 59 , 67 , 68 ] and should favor viral evolution to some degree due to the characteristic high-genetic variability from HIV. Several studies have reported lower levels of viral diversity in HICs compared with the levels in typical progressors [ 28 , 29 , 32 , 59 , 69 ]. Gijsberg et al estimated divergence rates of 0.9–1.9% over ten months for gag in HIV-1 samples from typical progressors [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that these gender-specific differences are one of the determining factors for whether an individual becomes EC or not. Indeed, the proportion of females within EC is higher compared to other groups of HIV-infected individuals ( Crowell et al, 2015 , de Azevedo et al, 2017 ). Despite extensive data on the male and female difference on disease outcome, research does not sufficiently take gender into account.…”
Section: Discussionmentioning
confidence: 91%